2012
DOI: 10.1590/s0034-737x2012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Divergência genética em genótipos de feijão comum cultivados em Mato Grosso do Sul

Abstract: Genetic divergence in common bean genotypes grown in the State of Mato Grosso do SulThe common bean breeding is based, mainly on the hybridization of cultivars and lines, so it is important to know the dissimilarity among the parents to obtain superior genotypes. The objectives of this work were: to cluster the genotypes by multivariate techniques using hierarchical method (nearest neighbor) and the canonical variables; to point the relative contribution of the analyzed traits for genetic dissimilarity and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 8 publications
3
22
0
5
Order By: Relevance
“…As in the present study, an evaluation of 13 genotypes (advanced lines and commercial cultivars) also detected that M100 was the trait that most contributed to the genetic dissimilarity in the common bean (Corrêa and Gonçalves, 2012). Similarly, Benin et al (2002) reported that the mass of thousand beans was the most important trait for the genetic dissimilarity in bean plant genotypes.…”
Section: Discussionsupporting
confidence: 80%
“…As in the present study, an evaluation of 13 genotypes (advanced lines and commercial cultivars) also detected that M100 was the trait that most contributed to the genetic dissimilarity in the common bean (Corrêa and Gonçalves, 2012). Similarly, Benin et al (2002) reported that the mass of thousand beans was the most important trait for the genetic dissimilarity in bean plant genotypes.…”
Section: Discussionsupporting
confidence: 80%
“…Similar genotypes are not recommended for use in genetic breeding programs by hybridization, because the genetic variability of segregating populations should not be restricted (Correa and Gonçalves, 2012); genetically similar parents tend to share many genes or alleles, and their crossing results in a low level of allelic heterozygosity (Cruz et al, 2014). The most divergent pair according to the Euclidian distance was 'Ametista' (1) and 'CNFC 10762' (10) (D = 2.00), while according to the Mahalanobis distance, it was 'BRS Esplendor' (3) and 'CNFC 10762' (10) (D 2 = 690.10).…”
Section: Resultsmentioning
confidence: 99%
“…The crop is highly susceptible to biotic and abiotic stressors, its architecture is inappropriate for mechanical harvesting, and its productivity and grain quality need improving . When starting a genetic breeding program, one of the most crucial aspects is the choice of parents (Correa and Gonçalves, 2012). Genetic divergence between individuals or populations is important in breeding programs that involve hybridization, because it facilitates the identification of parents that produce heterotic progeny and results in a higher probability of obtaining superior genotypes in segregating generations (Vidigal et al, 1997;Bertan et al, 2003;Benitez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of agronomic characters and multivariate techniques is common for plant breeding of different crops, such as maize (MORO; SILVEIRA; CARGNELUTTI FILHO, 2007, CARDOSO et al, 2009SIMON;KAMADA;MOITEIRO, 2012;MIRANDA, 2003), common bean (ELIAS et al, 2007;BARELLI et al, 2009;CORREA;GONÇALVES, 2012), castor bean (RODRIGUES et al, 2010) and cassava (ZUIN et al, 2009). According to Hallauer and Miranda Filho (1981), in addition to the high genetic divergence, the plant performance related to the desired characteristics in the desired environment is greatly important for choose the plant parents, in order to successfully obtaining superior lines.…”
Section: Introductionmentioning
confidence: 99%